Transcutaneous auricular vagus nerve stimulation on upper limb motor function with stroke: a functional near-infrared spectroscopy pilot study - Wang, Likai; Gao, Fei; Dai, Yongli; Wang, Zhan; Liang, Feng; Wu, Jingyi; Wang, Mengchun; Wang, Litong (Frontiers in Neuroscience, 2023)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) emerges as a promising neuromodulatory technique. However, taVNS uses left ear stimulation in stroke survivors with either left or right hemiparesis. Understanding its influence on the cortical responses is pivotal for optimizing post-stroke rehabilitation protocols. Objective The primary objective of this study was to elucidate the influence of taVNS on cortical responses in stroke patients presenting with either left or right hemiparesis and to discern its potential ramifications for upper limb rehabilitative processes. Methods We employed functional near-infrared spectroscopy (fNIRS) to ascertain patterns of cerebral activation in stroke patients as they engaged in a “block transfer” task. Additionally, the Lateralization Index (LI) was utilized to quantify the lateralization dynamics of cerebral functions. Results In patients exhibiting left-side hemiplegia, there was a notable increase in activation within the pre-motor and supplementary motor cortex (PMC-SMC) of the unaffected hemisphere as well as in the left Broca area. Conversely, those with right-side hemiplegia displayed heightened activation in the affected primary somatosensory cortex (PSC) region following treatment. Significantly, taVNS markedly amplified cerebral activation, with a pronounced impact on the left motor cortical network across both cohorts. Intriguingly, the LI showcased consistency, suggesting a harmonized enhancement across both compromised and uncompromised cerebral regions. Conclusion TaVNS can significantly bolster the activation within compromised cerebral territories, particularly within the left motor cortical domain, without destabilizing cerebral lateralization. TaVNS could play a pivotal role in enhancing upper limb functional restoration post-stroke through precise neuromodulatory and neuroplastic interventions.